Adolescent Vaginal Hygiene and Trichomonas vaginalis: A Focused Study in Balongbendo Village, Sidoarjo, East Java, Indonesia - Acivrida Mega Charisma; Farida Anwari; Bagus Nuzul Maulana (Jurnal Teknologi Laboratorium)
Trichomonas vaginalis is a protozoan parasite responsible for leucorrhoea, transmitted primarily through sexual contact, and commonly affecting the lower urogenital tract. According to the World Health Organization (WHO), the global incidence of trichomoniasis is estimated at 180 million cases annually. In the United States, the infection affects around 2-3 million women annually, with the organism also found in 30-40% of male sexual partners. This study aimed to examine the presence of Trichomonas vaginalis in adolescent urine samples and assess their vaginal hygiene practices in Balongbendo Village, Sidoarjo, East Java, Indonesia. Trichomonas vaginalis is widely prevalent across the globe, including both rural and urban areas. This focused study utilized both experimental and questionnaire-based approaches. Urine samples from 25 adolescents were analyzed directly for Trichomonas vaginalis presence, while a questionnaire was administered to assess personal hygiene practices, particularly focusing on genital care. Data were analyzed using One-Way ANOVA and Chi-Square tests to determine statistical significance and percentage distributions. The study identified Trichomonas vaginalis in 5 out of 25 urine samples, indicating a 20% prevalence among the participants. The majority of respondents demonstrated a solid understanding and practice of vaginal hygiene. The analysis revealed a statistically significant relationship between genital hygiene practices and the presence of Trichomonas vaginalis, with a p-value of 0.001 (p < 0.05). The findings indicate that while Trichomonas vaginalis remains present among adolescents in Balongbendo Village, the majority exhibit good vaginal hygiene practices, highlighting the importance of continuous education on genital care in preventing such infections.